State Expansion, Insurgent Resistance, and Territorial Control in Arauca 2002-2010 - Larrat-Smith, Charles (Revista Controversia, 2016)
When the state expands into territories contested by armed non-state actors with the goal of pacifying and integrating them into the broader national framework, the results are hardly the same across space and time. This state expansion will often witness a reduction in violence mirrored by an improvement in order. Quite frequently however, violence will increase as order worsens, thus begging the following question: how is the state able to reclaim control of certain disputed spaces easier than others? This article is a comparative study of three municipalities in northeast Colombia – Arauca, Arauquita, and Tame - which acted as laboratories for former President Álvaro Uribe’s state expansion campaign beginning in 2002. The former Colombian president selected these three locations, amongst others, to serve as a testing ground for an American counterinsurgency strategy which was designed to expel armed rebels from their havens and to recover this territory back into the national fold. However, whereas the military succeeded in defeating the insurgents in Arauca within five years of this intervention, Arauquita and Tame remain guerrilla strongholds to the present. These case studies provide an effective reference to examine past policies in the hopes that new ones can avoid similarly inconsistent outcomes. Key Words: Arauca, Arauquita, Tame, State expansion, Counterinsurgency, Guerrilla, Insurgent resistance, Territorial control EXPANSIÓN ESTATAL, RESISTENCIA INSURGENTE, Y CONTROL TERRITORIAL EN ARAUCA 2002-2010 Cuando el Estado se expande en los territorios en disputa por los grupos al margen de la ley, con el fin de apaciguar e integrarlos en el marco nacional, casi nunca los resultados son iguales a lo largo de tiempo y del espacio. A veces esta expansión estatal reduce la violencia y también la acompañada por un mejoramiento en el orden público. Sin embargo, frecuentemente en muchos casos la violencia aumenta y el orden público empeora, un fenómeno que nos lleva a la siguiente pregunta: ¿cómo se puede reclamar el control del Estado en unas zonas en disputa más fácil que en otras? Este artículo es un estudio comparado de tres municipios contiguos en el nororiente colombiano – Arauca, Arauquita, y Tame – que sirvieron como los primeros laboratorios para la política contrainsurgente del entonces presidente Álvaro Uribe Velez en el 2002. El ex-mandatorio eligió estos tres sitios, entre otros, para probar la estrategia contrainsurgente concebida en los EEUU, la cual fue diseñada para expulsar a los insurgentes de sus remansos y recuperar este territorio permanentemente. Cabe mencionar, que mientras la fuerza pública colombiana logró derrotar a los insurgentes en Arauca después de cinco años de dicha intervención, Arauquita y Tame siguen siendo bastiones guerrilleros hasta el presente. Estos tres casos proporcionan una buena referencia para evaluar las políticas de ayer, con la esperanza que las próximas podrían evadir los resultados tan inconsistentes. Palabras Clave: Arauca, Arauquita, Tame, Expansión estatal, Contrainsurgente, Guerrilla, Resistencia insurgente, Control territorial